Visualisasi Prinsip Kerja Pengapian Mesin Kendaraan Berbasis Graphical User Interface - - Universitas Surakarta, Ayu Fiska Nurryna (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2009)
ABSTRACT: Computer graphics is one area of computer science that studies how to simplify andimprove the interaction between humans and computers to create, store, manipulate the model imageof an object that is created with a computer. Computer graphics is one area of computer science thatcan improve the quality of information that will be presented to humans. With computer graphics, canbe created images - explanatory attractive image, making it easier to understand the informationoriginally presented by the line - a line of text. One example application is the manufacture of acomputer program that visualizes the physical system that is located relatively hidden, such as theignition system in a car engine. Visualization of the working principle of the engine ignition is what willbe discussed in this studyThe subject matter of this research is the science of computer graphics are applied in automotivescience. While the subject matter discussed was the visualization of the ignition system in a carengine. The discussion includes general knowledge about the elements of the ignition and its role andfunction, the stages of the working principle of the ignition with a dynamic image, the working principleof the ignition cycle as a whole is also accompanied by a dynamic image.With the formulation of this visual program, information about the ignition system is usually served withsheets of text, it becomes easier to imagine and understand because the text information aided bydrawings explanatory and dynamic image (moving image) which is called by the animation. Thevisualization program is expected to be useful as a tool for studying the working principle of the engineignition in theory.Keywords: Graphic AnimationABSTRAKSI: Grafika komputer adalah salah satu bidang ilmu komputer yang mempelajari caramempermudah dan meningkatkan interaksi antara manusia dan komputer dengan mencipta,menyimpan, memanipulasi gambar model suatu obyek yang dibuat dengan komputer. Grafikakomputer merupakan salah satu bidang ilmu komputer yang mampu meningkatkan kualitas informasiyang akan disajikan kepada manusia. Dengan grafika komputer, dapat diciptakan gambar – gambarpenjelas yang atraktif, sehingga mempermudah memahami informasi yang semula disajikan denganbaris – baris teks. Salah satu contoh aplikasinya adalah pembuatan program komputer yangmemvisualkan sistem fisik yang letaknya relatif tersembunyi, seperti sistem pengapian pada mesinmobil. Visualisasi prinsip kerja pengapian mesin mobil inilah yang akan dibahas dalam penelitian iniPokok bahasan penelitian ini adalah ilmu grafika komputer yang diaplikasikan dalam ilmuotomotif. Sedangkan materi pokok yang dibicarakan adalah visualisasi sistem pengapian pada mesinmobil. Pembahasan meliputi pengetahuan umum tentang elemen-elemen pengapian beserta perandan fungsinya, tahap-tahap prinsip kerja pengapian disertai gambar dinamis, siklus prinsip kerjapengapian secara keseluruhan juga disertai gambar dinamis.Dengan disusunnya program visual ini, informasi tentang sistem pengapian yang biasanyadisajikan dengan lembaran-lembaran teks, menjadi lebih mudah dibayangkan dan dipahami karenainformasi teks tersebut dibantu dengan gambar-gambar penjelas dan gambar dinamis (gambarbergerak) yang biasa disebut dengan animasi. Diharapkan program visualisasi ini dapat bergunasebagai alat bantu untuk mempelajari prinsip kerja pengapian mesin mobil secara teori.Kata Kunci : Animasi Grafis